DNA Methylation and Gene Expression of Matrix Metalloproteinase 9 Gene in Deficit and Non-deficit Schizophrenia - Gao, Ju; Yi, Hongwei; Tang, Xiaowei; Feng, Xiaotang; Yu, Miao; Sha, Weiwei; Wang, Xiang; Zhang, Xiaobin; Zhang, Xiangrong (Frontiers in Genetics, 2018)
The biological pathology of deficit schizophrenia (DS) remains unclear. Matrix metalloproteinase-9 (MMP-9) might be associated with neural plasticity and glutamate regulation, involved in schizophrenia pathogenesis. This study explores gene expression and DNA methylation of MMP-9 in peripheral blood mononuclear cells (PBMCs) and their relationship with clinical symptoms in DS and non-deficit schizophrenia (NDS). Pyrosequencing was used to determine DNA methylation at CpG sites in exon 4 and exon 5 of MMP-9 gene in 51 DS patients, 53 NDS patients and 50 healthy subjects (HC). RT-qPCR was used to detect MMP-9 gene expression. Clinical symptoms were assessed by BPRS, SANS and SAPS scales. MMP-9 gene expression in PBMCs was significantly higher in DS than NDS and HC subjects. Compared to NDS patients, DS patients had significantly lower DNA methylation at individual CpG sites in exon 4 and exon 5 of MMP-9 gene. Correlation analysis showed that DNA methylation in exon 4 was negatively correlated with gene expression in DS group. Positive correlation was found between MMP-9 gene expression and negative symptoms in total schizophrenic patients. The social amotivation factor of SANS and negative syndrome of BPRS was negatively correlated with DNA methylation of CpG5-1 in DS patients but not in NDS patients. DS patients showed a specific abnormality of peripheral MMP-9 gene expression and DNA methylation, indicating a pathological mechanism underlying DS as a specific subgroup of schizophrenia.